An Investigation of the Students` Opinion on the Use of Digital Storytelling in Learning English - Yentri Anggeraini (Universitas Lancang Kuning, 2020)
Various kinds of technology tools and media can be used to facilitate the leaching and learning English in this era. One of them is digital storytelling. It is a multimedia text including images, audio, or video accompanied by a narrated soundtrack to tell a story or give information. It combines the functions of visual, verbal, and audio those are important for language comprehension and skills. This present study aimed at investigating the students` opinions on the use of digital storytelling in EFL classroom. The questionnaire and interview were distributed to 31 participants as the main data. The results indicated that 84% students like learning English through digital storytelling, 81% of them enjoy presenting and sharing their digital literacy, and 77% of them argue that digital storytelling can motivate them to read a lot. It can be derived that digital storytelling makes the students participate actively during the learning process, allows the students to work collaboratively, and provide the students to be digitally literate.